5.1 Mathematical Induction

p334
Ex: 1, 2, 3, 5, 6, 8, 9, 10, 11

To prove a statement P(n)P(n) is true for every nn>nthresholdn \mid n > n_{threshold} (positive integer)
1. Basic step Show P(nthreshold)P(n_{threshold}) is true.
2. Hypothesis Assume the statement for a value of n=k,P(k)n=k, P(k) is true .
3. Induction step Prove for n=k+1,P(k+1)n=k+1, P(k+1) is true.

EXAMPLE 1
Show that if nn is a positive integer, then 1+2++n=n(n+1)21 + 2 + \cdots + n = \frac{n(n+1)}{2}

EXAMPLE 2
Conjecture a formula for the sum of the first n positive odd integers. Then prove your conjecture using mathematical induction.

EXAMPLE 3
Use mathematical induction to show that 1+2+22++2n=2n+111 + 2 + 2^2 + \cdots + 2^n = 2^{n+1} - 1

EXAMPLE 5
Use mathematical induction to prove the inequality n<2nn <2^n for all positive integers.

EXAMPLE 6
Use mathematical induction to prove that 2n<n!2^n < n! for every integer nn with n4n \ges 4. (Note that this inequality is false for n=1,2n = 1, 2, and 33.)

EXAMPLE 8
Use mathematical induction to prove that n3nn^3 - n is divisible by 33 whenever nn is a positive integer. (Note that this is the statement with p=3p = 3 of Fermat’s little theorem, which is Theorem 3 of Section 4.4.)

EXAMPLE 9
Use mathematical induction to prove that 7n+2+82n+17^{n+2} + 8^{2n+1} is divisible by 5757 for every nonnegative integer nn.

EXAMPLE 10
The Number of Subsets of a Finite Set Use mathematical induction to show that if SS is a finite set with nn elements, where nn is a nonnegative integer, then SS has 2n2^n subsets. (We will prove this result directly in several ways in Chapter 6.)

EXAMPLE 11
Use mathematical induction to prove the following generalization of one of De Morgan's laws:

j=1nAj=j=1nAj\begin{aligned} \overline{\bigcap_{j=1}^n A_j} = \bigcup_{j=1}^n \overline{A_j} \end{aligned}

whenever A1,A2,,AnA_1, A_2, \cdots, A_n are subsets of a universal set UU and n2n\ges 2

Homework

p350: 6, 14, 15, 20, 21, 31, 32, 34, 36, 43

6. Prove that 11!+22!++nn!=(n+1)!11 \cdot 1! + 2 \cdot 2!+ \cdots + n \cdot n! = (n + 1)! - 1 whenever nn is a positive integer.

Solution

Proof:
Let P(n)P(n) be the statement 11!+22!++nn!=(n+1)!11 \cdot 1! + 2 \cdot 2!+ \cdots + n \cdot n! = (n + 1)! - 1 for all every integer nn.
Basic step. P(1)P(1) is true, because 11=(1+1)11=11\cdot 1 = (1+1) \cdot 1 -1 = 1
Hypothesis. Assume P(n)P(n) is true for n=kn=k

11!+22!++kk!=(k+1)!11 \cdot 1! + 2 \cdot 2!+ \cdots + k \cdot k! = (k + 1)! - 1

Inductive step We need to prove P(k+1)P(k+1), namely, 11!+22!++kk!+(k+1)(k+1)=(k+2)!11 \cdot 1! + 2 \cdot 2!+ \cdots + k \cdot k! + (k+1)\cdot (k+1) = (k + 2)! - 1.

11!+22!++kk!+(k+1)(k+1)!=(k+1)!1+(k+1)(k+1)!By Hypothesis=(k+2)(k+1)!1=(k+2)!1\begin{aligned} &1 \cdot 1! + 2 \cdot 2!+ \cdots + k \cdot k! + (k+1)\cdot (k+1)!\\ &= (k+1)! - 1 + (k+1)\cdot (k+1)! &\text{By Hypothesis}\\ &= (k+2)(k+1)! - 1\\ &= (k+2)! - 1 \end{aligned}

By induction, P(n)P(n) is true.

14. Prove that for every positive integer nn, k=1nk2k=(n1)2n+1+2\sum_{k=1}^n{k2^k} = (n-1)2^{n+1} + 2.

Solution

Proof:
Let P(n)P(n) be the statement k=1nk2k=(n1)2n+1+2\sum_{k=1}^n{k2^k} = (n-1)2^{n+1} + 2, for every positive integer nn.
Basic step. P(1)P(1) is true, because k=11k2k=121=(11)21+1+2=2\sum_{k=1}^1{k2^k} = 1 \cdot 2^1 = (1-1)\cdot 2^{1+1} + 2 = 2.
Hypothesis. Assume P(n)P(n) is true for n=mn=m

k=1mk2k=(m1)2m+1+2\sum_{k=1}^m{k2^k} = (m-1)2^{m+1} + 2

Inductive step We need to prove P(m+1)P(m+1), namely k=1m+1k2k=(m)2m+2+2\sum_{k=1}^{m+1}{k2^k} = (m)2^{m+2} + 2, is true.

k=1m+1k2k=k=1mk2k+(m+1)2m+1=(m1)2m+1+2+(m+1)2m+1By Hypothesis=(m1+m+1)2m+1+2=m22m+1+2=m2m+2+2\begin{aligned} \sum_{k=1}^{m+1}{k2^k} &= \underline{\sum_{k=1}^{m}{k2^k}} + (m+1)2^{m+1} \\ &= \underline{(m-1)2^{m+1} + 2} + (m+1)2^{m+1} &\text{By Hypothesis}\\ &= (m-1 + m+1)2^{m+1} + 2\\ &= m \cdot 2 \cdot 2^{m+1} + 2\\ &= m2^{m+2} + 2 \end{aligned}

By induction, P(n)P(n) is true.

15. Prove that for every positive integer nn, 12+23++n(n+1)=n(n+1)(n+2)/31\cdot 2 + 2\cdot 3 + \cdots + n(n + 1) = n(n + 1)(n + 2)/3.

Solution

Proof:
Let P(n)P(n) be the statement 12+23++n(n+1)=n(n+1)(n+2)/31\cdot 2 + 2\cdot 3 + \cdots + n(n + 1) = n(n + 1)(n + 2)/3, for every positive integer nn.
Basic step. P(1)P(1) is true, because 12=1(1+1)(1+2)3=21\cdot 2 = \dfrac{1\cdot (1+1)(1+2)}{3} = 2.
Hypothesis. Assume P(n)P(n) is true for n=kn=k

12+23++k(k+1)=k(k+1)(k+2)31\cdot 2 + 2\cdot 3 + \cdots + k(k + 1) = \frac{k(k + 1)(k + 2)}{3}

Inductive step We need to prove P(k+1)P(k+1), namely 12+23++k(k+1)+(k+1)(k+2)=(k+1)(k+2)(k+3)31\cdot 2 + 2\cdot 3 + \cdots + k(k+1)+(k+1)(k+2)= \dfrac{(k+1)(k+2)(k+3)}{3}, is true.

12+23++k(k+1)+(k+1)(k+2)=k(k+1)(k+2)3+(k+1)(k+2)By hypothesis=k(k+1)(k+2)3+3(k+1)(k+2)3=(k+1)(k+2)(k+3)3\begin{aligned} &1\cdot 2 + 2\cdot 3 + \cdots + k(k+1)+(k+1)(k+2)\\ &= \frac{k(k + 1)(k + 2)}{3} + (k+1)(k+2) &\text{By hypothesis}\\ &= \frac{k(k + 1)(k + 2)}{3} + \frac{3(k + 1)(k + 2)}{3}\\ &= \frac{(k + 1)(k + 2)(k+3)}{3} \end{aligned}

By induction, P(n)P(n) is true.

20. Prove that 3n<n!3^n< n! if nn is an integer greater than 6.

Solution

Let P(n)P(n) be the statement 3n<n!3^n< n! for integer nn greater than 6.
Basic step P(7)P(7) is true, because 37=2187<7!=50403^7=2187 < 7!=5040.
Hypothesis. Assume P(n)P(n) is true for n=kn=k,

3k<k!3^k< k!

Inductive step. We need to prove P(k+1)P(k+1), namely 3k+1<(k+1)!3^{k+1}< (k+1)!, is true.

3k+1=33k<3k!By hypothesisk+1>n+1>6+1=7>33k+1=33k<(k+1)k!=(k+1)!\begin{aligned} 3^{k+1} = 3 \cdot 3^k < 3 \cdot k! \quad \text{By hypothesis}\\ \because k+1> n+1 > 6+1 =7 > 3\\ \therefore 3^{k+1} = 3 \cdot 3^k < (k+1) \cdot k! = (k+1)! \end{aligned}

By induction, P(n)P(n) is true.

21. Prove that 2n>n22^n > n^2 if nn is an integer greater than 4.

Solution

Let P(n)P(n) be the statement 2n>n22^n > n^2 for integer nn greater than 4.
Basic step P(5)P(5) is true, because 25=32>52=252^5=32 > 5^2=25.
Hypothesis. Assume P(n)P(n) is true for n=kn=k,

2n>n22^n> n^2

Inductive step. We need to prove P(k+1)P(k+1), namely 2k+1>(k+1)22^{k+1}> (k+1)^2, is true.

2k+1=22k>2k2By hypothesis2k2(k+1)2=2k2k22k1=(k1)22k>4(k1)22>02k2(k+1)2>02k2>(k+1)22k+1>(k+1)2\begin{aligned} 2^{k+1} =2 \cdot 2^k > 2k^2 \quad \text{By hypothesis}\\ 2k^2 - (k+1)^2 = 2k^2-k^2-2k-1 = (k-1)^2 - 2\\ \because k>4\\ \therefore (k-1)^2 -2 > 0\\ \therefore 2k^2 - (k+1)^2 > 0\\ \therefore 2k^2 > (k+1)^2\\ \therefore 2^{k+1} > (k+1)^2 \end{aligned}

By induction, P(n)P(n) is true.

31. Prove that 22 divides n2+nn^2 + n whenever nn is a positive integer.

Solution

Let P(n)P(n) be the statement 2n2+n2 \lvert n^2 + n for positive integer nn.
Basic step P(1)P(1) is true, because 12+12=1\dfrac{1^2+1}{2} = 1.
Hypothesis. Assume P(n)P(n) is true for n=kn=k,

2k2+k2 \lvert k^2 + k

Inductive step. We need to prove P(k+1)P(k+1), namely 2(k+1)2+k+12 \lvert (k+1)^2 + k+1, is true.

(k+1)2+k+1=k2+2k+1+k+1=k2+k+2(k+1)2k2+k and 22(k+1)2k2+k+2(k+1) or 2(k+1)2+k+1\begin{aligned} (k+1)^2 + k+1 &= k^2+2k+1+k+1\\ &= k^2+k + 2(k+1)\\ &\because 2 \lvert k^2+k \text{ and } 2 \lvert 2(k+1)\\ &\therefore 2 \lvert k^2+k + 2(k+1) \text { or } 2 \lvert (k+1)^2 + k+1 \end{aligned}

By induction, P(n)P(n) is true.

32. Prove that 33 divides n3+2nn^3 + 2n whenever nn is a positive integer.

Solution

Let P(n)P(n) be the statement 3n3+2n3 \lvert n^3 + 2n for positive integer nn.
Basic step P(1)P(1) is true, because 13+213=1\dfrac{1^3+2 \cdot 1}{3} = 1.
Hypothesis. Assume P(n)P(n) is true for n=kn=k,

3k3+2k3 \lvert k^3 + 2k

Inductive step. We need to prove P(k+1)P(k+1), namely 3(k+1)3+2(k+1)3 \lvert (k+1)^3 + 2(k+1), is true.

(k+1)3+2(k+1)=k3+3k2+3k+1+2k+2=(k3+2k)+(3k2+3k+3)=(k3+2k)+3(k2+k+1)3(k3+2k) and 33(k2+k+1)3(k3+2k)+3(k2+k+1) or 3(k+1)3+2(k+1)\begin{aligned} (k+1)^3 + 2(k+1) &= k^3+3k^2+3k+1 + 2k+2\\ &= (k^3+2k) + (3k^2+3k+3)\\ &= (k^3+2k) + 3(k^2+k+1)\\ &\because 3 \lvert (k^3+2k) \text{ and } 3 \lvert 3(k^2+k+1)\\ &\therefore 3 \lvert (k^3+2k) + 3(k^2+k+1) \text{ or } 3\lvert (k+1)^3 + 2(k+1) \end{aligned}

By induction, P(n)P(n) is true.

34.Prove that 66 divides n3nn^3 - n whenever nn is a nonnegative
integer.

Solution

Let P(n)P(n) be the statement 6n3n6 \lvert n^3 - n for positive integer nn.
Basic step P(1)P(1) is true, because 1316=0\dfrac{1^3-1}{6} = 0.
Hypothesis. Assume P(n)P(n) is true for n=kn=k,

6k3k6 \lvert k^3 - k

Inductive step. We need to prove P(k+1)P(k+1), namely 6(k+1)3(k+1)6 \lvert (k+1)^3 -(k+1), is true.

(k+1)3(k+1)=k3+3k2+3k+1k1=(k3k)+3k(k+1)\begin{aligned} (k+1)^3 -(k+1)&= k^3+ 3k^2+3k+1-k-1\\ &= (k^3 -k) + 3k(k+1) \end{aligned}

As 6(k3k)6|(k^3 -k), we need to to prove 63k(k+1)6|3k(k+1).
Because one in kk and k+1k+1 is even, k(k+1)k(k+1) is even. Thus 63k(k+1)6|3k(k+1).
That is 6(k3k)+3k(k+1)6\lvert (k^3 -k) + 3k(k+1)
By induction, P(n)P(n) is true.

36.Prove that 21 divides 4n+1+52n14^{n+1} + 5^{2n-1} whenever nn is a positive integer.

Solution

Let P(n)P(n) be the statement 214n+1+52n121 \lvert 4^{n+1} + 5^{2n-1} for positive integer nn.
Basic step P(1)P(1) is true, because 41+1+52121=2121=1\dfrac{4^{1+1} + 5^{2-1}}{21} = \dfrac{21}{21} = 1.
Hypothesis. Assume P(n)P(n) is true for n=kn=k,

214k+1+52k121 \lvert 4^{k+1} + 5^{2k-1}

Inductive step. We need to prove P(k+1)P(k+1), namely 214(k+1)+1+52(k+1)121 \lvert 4^{(k+1)+1} + 5^{2(k+1)-1}, is true.

4(k+1)+1+52(k+1)1=44k+1+2552k1=254k+1+2552k1214k+1=25(4k+1+52k1)214k+121(4k+1+52k1)Hypothesis2125(4k+1+52k1)21214k+12125(4k+1+52k1)214k+1 or 214(k+1)+1+52(k+1)1\begin{aligned} 4^{(k+1)+1} + 5^{2(k+1)-1} &= 4\cdot 4^{k+1} + 25 \cdot 5^{2k-1}\\ &= 25\cdot 4^{k+1} + 25 \cdot 5^{2k-1} - 21\cdot 4^{k+1}\\ &= 25\cdot(4^{k+1} + 5^{2k-1}) - 21\cdot 4^{k+1}\\ &\because 21 \lvert (4^{k+1} + 5^{2k-1}) \quad \text{Hypothesis}\\ &\therefore 21 \lvert 25\cdot(4^{k+1} + 5^{2k-1})\\ &\because 21 \lvert 21\cdot 4^{k+1}\\ &\therefore 21 \lvert 25\cdot(4^{k+1} + 5^{2k-1}) - 21\cdot 4^{k+1} \text{ or } 21 \lvert 4^{(k+1)+1} + 5^{2(k+1)-1} \end{aligned}

By induction, P(n)P(n) is true.

43. Prove that if A1,A2,...,AnA1, A2,...,An are subsets of a universal set UU, then k=1nAk=k=1nAk\overline{\bigcup_{k=1}^n A_k} = \bigcap_{k=1}^n \overline{A_k}.

Solution

Let P(n)P(n) be the statement k=1nAk=k=1nAk\overline{\bigcup_{k=1}^n A_k} = \bigcap_{k=1}^n \overline{A_k}.
Basic step. P(1)P(1) is true, because k=11Ak=A1=k=11A1\overline{\bigcup_{k=1}^1 A_k} = \overline{A_1} = \bigcap_{k=1}^1 \overline A_1.
Hypothesis. Assume P(n)P(n) is true for n=mn=m,

k=1mAk=k=1mAk\overline{\bigcup_{k=1}^m A_k} = \bigcap_{k=1}^m \overline{A_k}

Inductive step. We need to prove P(k+1)P(k+1), namely k=1m+1Ak=k=1m+1Ak\overline{\bigcup_{k=1}^{m+1} A_k} = \bigcap_{k=1}^{m+1} \overline{A_k}, is true.

k=1m+1Ak=k=1mAkAm+1Defition of union of sets=k=1mAkAm+1De Morgan’s Law=k=1mAkAm+1By Hypothesis=k=1m+1AkDefition of intersection of sets\begin{aligned} \overline{\bigcup_{k=1}^{m+1} A_k} &= \overline{\bigcup_{k=1}^{m} A_k \cup A_{m+1}} &\text{Defition of union of sets}\\ &= \overline{\bigcup_{k=1}^{m} A_k} \cap \overline{A_{m+1}} &\text{De Morgan's Law}\\ &= \bigcap_{k=1}^{m} \overline{A_k} \cap \overline{A_{m+1}} &\text{By Hypothesis}\\ &= \bigcap_{k=1}^{m+1} \overline{A_k} &\text{Defition of intersection of sets}\\ \end{aligned}

By induction, P(n)P(n) is true.